Alkaloid profiling, antimicrobial and cytotoxic activities of Argania spinosa leaf extracts - Fatima Zahra Lafdil; Fahd Kandsi; Kaouthar EL Birgui; Chaimaa Sabiri; Hicham Lafdil; Othman EL Faqer; Hassane Mekhfi; Raffaele Conte (South African Journal of Botany, 2026)

Phenolic-rich fractions from dittrichia viscosa against foodborne pathogens: integrating in vitro antibacterial activity, UHPLC–MS/MS profiling, and molecular docking analysis - Rania Jerada; Mohamed Ouabane; Raffaele Conte; Abdelmoula El Ouardi; Ali Mzali; Hicham Dahak; Hicham Harhar; Mohammed Bouachrine; Riaz Ullah; Amal Alotaibi; Abdelhakim Bouyahya; Brahim Mojemmi; et al. (Plant Biosystems, 2026)

Field evidence of enzootic chytrid infection in a Mediterranean mountain amphibian - Antonio Romano; Raffaele Di Biasi; Lorenzo Dondero; Elena Grasselli; Antonio Luca Conte; Donata Coppola; Camilla Menestrina (Biologia, 2026)
Emerging infectious diseases drive amphibian population declines worldwide. The chytrid fungus Batrachochytrium dendrobatidis ( Bd ) has caused severe losses, although impacts vary among species and environments. The Apennine yellow-bellied toad ( Bombina variegata pachypus ), endemic to Italy, has declined since the 1990s, yet Bd status in southern populations is poorly known. In 2024, we screened three populations within the Appennino Lucano, Val d Agri e Lagonegrese National Park (southern Italy). Fifty adults, representing nearly the entire local populations, were sampled from three artificial aquatic breeding sites (livestock drinking-troughs). Quantitative PCR detected Bd DNA in two asymptomatic individuals (4% prevalence; 10.05 and 18.99 GE µL⁻ 1 ). Low prevalence and absence of clinical signs are consistent with enzootic persistence rather than an epizootic outbreak. The species’ thermophilous breeding ecology, relying on shallow, sun-exposed water bodies, may contribute to environmental conditions less favourable to Bd growth. Genetic diversity and skin microbiome defences may further enhance resistance. However, habitat fragmentation could increase vulnerability by reducing connectivity and recolonization. Our results highlight the potential role of open, sunlit rural water bodies in supporting reproduction and potentially limiting disease impact.

Green-sourced polyphenols for ocular health: A sustainable NADES-based approach to dry eye disease treatment - Fabrizia Sepe; Ezia Costanzo; Viviana Chiappini; Loredana Marcolongo; Sabrina Margarucci; Orsolina Petillo; Giuseppe Ruggiero; Diego Circolo; Raffaele Conte; Anna Valentino; Gianfranco Peluso; Anna Calarco (Sustainable Chemistry and Pharmacy, 2026)

Sensing human health from Space: An assessment of applications and big data platforms - Dhritiraj Sengupta; Filipe Girbal Brandão; Shubha Sathyendranath; Gemma Kulk; Annamaria Conte; Carla Ippoliti; Luca Candeloro; Monica Bucciarelli; David Moffat; William Wint; Marcello Maranesi; Raffaele Scarano; et al. (Remote Sensing Applications: Society and Environment, 2025)

Antidiabetic and aldose reductase inhibitory activity and LC-MS/MS compositional polyphenol determination of aqueous extract of Ammodaucus leucotrichus fruits - Saliha Bouknana; Fatima Zahra Lafdil; Fahd Kandsi; Mounia Driouech; Raffaele Conte; Driss Bouknana; Abderrahim Ziyyat; Hassane Mekhfi; Abdelkhaleq Legssyer; Mohamed Bnouham (Biocatalysis and Agricultural Biotechnology, 2024)

Remdesivir treatment and clinical outcome in non-severe hospitalized COVID-19 patients: a propensity score matching multicenter Italian hospital experience - Emilio Attena; Alfredo Caturano; Anna Annunziata; Alberto Enrico Maraolo; Annunziata De Rosa; Francesco Maria Fusco; Geza Halasz; Valeria Dall’Ospedale; Maddalena Conte; Valentina Parisi; Raffaele Galiero; Ferdinando Carlo Sasso; et al. (European Journal of Clinical Pharmacology, 2023)
Introduction Remdesivir exerts positive effects on clinical improvement, even though it seems not to affect mortality among COVID-19 patients; moreover, it was associated with the occurence of marked bradycardia. Methods We retrospectively evaluated 989 consecutive patients with non-severe COVID-19 (SpO 2 ≥ 94% on room air) admitted from October 2020 to July 2021 at five Italian hospitals. Propensity score matching allowed to obtain a comparable control group. Primary endpoints were bradycardia onset (heart rate < 50 bpm), acute respiratory distress syndrome (ARDS) in need of intubation and mortality. Results A total of 200 patients (20.2%) received remdesivir, while 789 standard of care (79.8%). In the matched cohorts, severe ARDS in need of intubation was experienced by 70 patients (17.5%), significantly higher in the control group (68% vs. 31%; p < 0.0001). Conversely, bradycardia, experienced by 53 patients (12%), was significantly higher in the remdesivir subgroup (20% vs. 1.1%; p < 0.0001). During follow-up, all-cause mortality was 15% ( N = 62), significantly higher in the control group (76% vs. 24%; log-rank p < 0.0001), as shown at the Kaplan–Meier (KM) analysis. KM furthermore showed a significantly higher risk of severe ARDS in need of intubation among controls (log-rank p < 0.001), while an increased risk of bradycardia onset in the remdesivir group (log-rank p < 0.001). Multivariable logistic regression showed a protective role of remdesivir for both ARDS in need of intubation (OR 0.50, 95%CI 0.29–0.85; p = 0.01) and mortality (OR 0.18, 95%CI 0.09–0.39; p < 0.0001). Conclusions Remdesivir treatment emerged as associated with reduced risk of severe acute respiratory distress syndrome in need of intubation and mortality. Remdesivir-induced bradycardia was not associated with worse outcome.

The LIFE PERSUADED project approach on phthalates and bisphenol A biomonitoring in Italian mother-child pairs linking exposure and juvenile diseases - Cinzia La Rocca; Francesca Maranghi; Sabrina Tait; Roberta Tassinari; Francesca Baldi; Giorgia Bottaro; Emma Buzzigoli; Fabrizia Carli; Stefano Cianfarani; Raffaele Conte; Annalisa Deodati; Amalia Gastaldelli; et al. (Environmental Science and Pollution Research, 2018)